2003
DOI: 10.1016/s0735-1097(03)00943-4
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of risk for first age-related cardiovascular events in an elderly population: the incremental value of echocardiography

Abstract: Echocardiography enhanced prediction of first cardiovascular events in this referral-based elderly cohort. Its role in risk stratification for primary prevention of these events in the community warrants further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
159
1
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(175 citation statements)
references
References 21 publications
8
159
1
7
Order By: Relevance
“…The association of diastolic dysfunction with abnormal small artery remodeling was further strengthened by significant correlations between left atrial volume and both small artery wall thickness and the wall‐to‐lumen ratio. Left atrial dilatation is invariably present in heart failure, irrespective of ejection fraction,28 and it is established that left atrial volume increases proportionally with the severity of diastolic dysfunction, independent of comorbid risks 29. As such, left atrial volume is felt to be one of the most sensitive and specific measures to differentiate between HFpEF and hypertensive changes to the heart 28.…”
Section: Discussionmentioning
confidence: 99%
“…The association of diastolic dysfunction with abnormal small artery remodeling was further strengthened by significant correlations between left atrial volume and both small artery wall thickness and the wall‐to‐lumen ratio. Left atrial dilatation is invariably present in heart failure, irrespective of ejection fraction,28 and it is established that left atrial volume increases proportionally with the severity of diastolic dysfunction, independent of comorbid risks 29. As such, left atrial volume is felt to be one of the most sensitive and specific measures to differentiate between HFpEF and hypertensive changes to the heart 28.…”
Section: Discussionmentioning
confidence: 99%
“…[311][312][313][314][315][316] In the absence of MVD, an increase in LA size most commonly reflects increased wall tension as a result of increased LA pressure, [317][318][319][320] as well as impairment in LA function secondary to atrial myopathy. 321,322 A clear relationship exists between an enlarged LA and the incidence of atrial fibrillation and stroke, [323][324][325][326][327][328][329][330][331][332] risk for overall mortality after myocardial infarction, 321,322,333,334 risk for death and hospitalization in patients with dilated cardiomyopathy, [335][336][337][338][339][340][341][342][343][344] and major cardiac events or death in patients with diabetes mellitus.…”
Section: Imaging Techniques To Detect Atrial Cardiomyopathies Mappingmentioning
confidence: 99%
“…LA volume has prognostic value for future adverse cardiovascular events including myocardial infarction, cerebrovascular events, atrial fibrillation, HF as well as cardiac and all‐cause mortality 124 , 125 , 126 , 127 . Tsang, et al 118 demonstrated that increasing LA volume stratified risks of developing such adverse events.…”
Section: La Size Volume and Functionmentioning
confidence: 99%